2021
DOI: 10.3390/agronomy11050876
|View full text |Cite
|
Sign up to set email alerts
|

Production of Virus-Free Garlic Plants through Somatic Embryogenesis

Abstract: The present study was conducted to establish a protocol for the regeneration of virus-free garlic plants through somatic embryogenesis of two Croatian garlic ecotypes. Basal parts of cloves from mother plants were cultured on a full Murashige and Skoog (MS) or modified MS medium (¼ of KNO3 and NH4NO3 and 2xMgSO4) containing 0.1 mg L−1 2,4-dichlorophenoxyacetic acid (2,4-D) or 1 mg L−1 2,4-D + 0.5 mg L−1 kinetin (Kin) and representing four different treatments. Plants were regenerated in MS medium containing 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The efficiency of the technique depends on the type and the accumulation level of a virus in the plant, its physiology, and plants’ resistance level [ 47 ]. Techniques such as tissue culture (meristem culture, somatic embryogenesis); cold, chemical, and heat treatments; or tissue culture combined with cold, chemical, and heat treatments have been applied to eliminate viruses [ 14 , 28 , 37 , 39 , 48 , 49 , 50 ]. The success of any approach does not depend only on virus elimination but also on the successful recovery of virus-free garlic plants.…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of the technique depends on the type and the accumulation level of a virus in the plant, its physiology, and plants’ resistance level [ 47 ]. Techniques such as tissue culture (meristem culture, somatic embryogenesis); cold, chemical, and heat treatments; or tissue culture combined with cold, chemical, and heat treatments have been applied to eliminate viruses [ 14 , 28 , 37 , 39 , 48 , 49 , 50 ]. The success of any approach does not depend only on virus elimination but also on the successful recovery of virus-free garlic plants.…”
Section: Discussionmentioning
confidence: 99%
“…Also, virus-free garlic plants were regenerated through somatic embryogenesis from basal parts of cloves of two Croatian garlic ecotypes on MS medium containing 0.1 mg/L 2,4-D. The results showed that the elimination of onion yellow dwarf virus (OYDV), leek yellow stripe virus (LYSV) and garlic common latent virus (GCLV) was as successful as other methods 45 . Somatic embryogenesis of tepal flower tissue in Hippeastrum hybridum was performed on MS medium containing 0.5 mg/L 2,4-D and 1 mg/L TDZ.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the different garlic ecotypes the elimination efficiencies were between 13 and 63%, which shows a strong genotype effect in SE-based elimination [46]. In cassava, the age of the callus tissues and long regeneration period probably reduced the efficiency for the 'Ankrah' cultivar [31].…”
Section: Genotype Effectmentioning
confidence: 99%